Join IDNLearn.com to access a wealth of knowledge and get your questions answered by experts. Our platform provides accurate, detailed responses to help you navigate any topic with ease.
Sagot :
Answer: 1.
Given: S is the midpoint of RT
PR=PT
To Prove: PRS=PTS
Step-by-step explanation:
If PR=PT in a triangle PRT, then the triangle is isosceles triangle.
Therefore, ∠PRT=∠PTR (opposite angles of an isosceles triangle are equal)
In ▲PRS and ▲PTS
PR=PT
∠PRT=∠PTR
PS=PS (PS is common)
therefore, ▲PRS≅▲PTS
Therefore, ∠PRS=∠PTS
Hence proved.
Answer: 2.
Given: E is the midpoint of AB and CD.
To Prove: AEC=BED
Step-by-step explanation:
If AB and CD are the diagonals of rectangle, then
diagonals AB=CD, sides AC=BD and AD=BC
In ▲AEC and ▲BED,
∠AEC=∠BED(vertically opposite angles)
AE=BE
AC=BD
therefore, ▲AEC≅▲BED
Therefore, ∠AEC=∠BED
Hence Proved.
The proofing of each part should be explained below.
Prove:
a.
In the case when
PR=PT in a triangle PRT,
So the triangle is an isosceles triangle.
Therefore, ∠PRT=∠PTR
Now
In ΔPRS and ΔPTS
PR=PT
So,
∠PRT=∠PTR
So,
PS=PS (PS is common)
ΔPRS≅ΔPTS
Hence proved.
2.
In the case when AB and CD are the diagonals of the rectangle,
So,
diagonals AB=CD, sides AC=BD and AD=BC
In ΔAEC and ΔBED,
So,
∠AEC=∠BED
That means
AE=BE
AC=BD
therefore, ΔAEC≅ΔBED
Hence Proved.
Learn more about the midpoint here; https://brainly.com/question/24600215
Thank you for participating in our discussion. We value every contribution. Keep sharing knowledge and helping others find the answers they need. Let's create a dynamic and informative learning environment together. For precise answers, trust IDNLearn.com. Thank you for visiting, and we look forward to helping you again soon.